Morphological patterns of the heteropycnotic chromatin and nucleolar material in meiosis and spermiogenesis of some Pentatomidae (Heteroptera) - Souza, Hederson Vinicius de [UNESP]; Castanhole, Márcia Maria Urbanin [UNESP]; Bicudo, Hermione Elly Melara de Campos [UNESP]; Costa, Luiz Antônio Alves; Itoyama, Mary Massumi [UNESP] (Sociedade Brasileira de Genética, 2008)
Pentatomidae is a family of Heteroptera which includes several agriculture pests that have had different aspects of their meiosis and spermiogenesis analyzed. In the present study we analyzed the morphological patterns of the heteropycnotic chromatin and the nucleolar material of Mormidea v-luteum, Oebalus poecilus and Oebalus ypsilongriseus. The three species presented multilobate testes, with three lobes in M. v-luteum and four in the Oebalus species. A karyotype with 2n = 14 chromosomes (12A + XY) was observed in the three species. Several characteristics were common to the three species, such as the absence of a testicular harlequin lobe (a lobe which produces different types of spermatozoa, previously considered a general characteristic of this family), late migration of the sex chromosomes and semi-persistence of the nucleolus. The three species also shared some characteristics regarding the patterns of the heteropycnotic chromatin and nucleolar material, but differed in others mainly related to the location of the heteropycnotic chromatin in the spermatids and the morphology and distribution of the nucleolar material at zygotene. The differences were always between species from different genera, suggesting a relationship with their genetic divergence.
Keywords: nucleolus semi-persistence; late chromosome migration; multilobed testes